(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Oyster mushroom is a mushroom that is quite in demand by the people of Pekanbaru City. One of the oyster mushroom producers in Pekanbaru is a young entrepreneur named Solihin who is a student of the Department of Agrotechnology, Riau University. Oyster mushroom production ranges from 15-40 kg/day. The high production of mushrooms is supported by the number of baglogs owned by Solihin. After being used to produce mushrooms, this baglog will of course become waste. The high content of organic matter in baglog waste makes baglog waste a potential medium for the development of African Night Crawlers (ANC) worms. Furthermore, the remaining growth media for this worm can be used as vermicompost fertilizer. Therefore, the purpose of this service is to provide assistance in the cultivation of ANC worms to entrepreneurs who are partners in this service. Based on the results of the service carried out, partners have succeeded in developing by-products other than oyster mushrooms into useful and selling products which can certainly increase partners’ income. In addition, partners are also developing fish farming as a continuation of the use of ANC worms as fish feed. This is because ANC worms are a high source of protein for fish feed. Through this service activity, the development of integrated agricultural agribusiness has been realized.